Phase-specific effects of guar meal and β-mannanase on growth performance and nutrient digestibility in broilers - Haroon Ur Rashid; Taimoor Khan; Muhammad Tahir; Muhammad Daud; Damiano Cavallini; Giovanni Buonaiuto (Tropical Animal Health and Production, 2026)
This study evaluated the phase-specific effects of dietary guar meal (GM) inclusion, with or without β-mannanase supplementation, on growth performance, nutrient digestibility, and energy utilization in broiler chickens. A total of 300 male Ross 308 broilers were assigned to eight experimental diets in a 4 × 2 factorial arrangement, consisting of four GM inclusion levels (0%, 4%, 8%, and 12%) with or without β-mannanase supplementation (0.35 g/kg), and were evaluated during the starter (7–21 d) and grower (22–35 d) phases. During the starter phase, broilers fed 4% GM supplemented with β-mannanase achieved growth performance comparable to the control diet, whereas increasing GM inclusion significantly reduced body weight gain, crude protein digestibility, and apparent metabolizable energy (AME; P < 0.05). β-mannanase supplementation partially alleviated these negative effects and fully restored crude protein digestibility at 4% GM. During the grower phase, broilers tolerated up to 8% GM without major reductions in growth performance, whereas 12% GM consistently impaired productive responses. Enzyme supplementation further enhanced body weight gain and protein digestibility across GM inclusion levels; however, its efficacy declined at 12% GM, where performance and energy utilization remained significantly lower than the control diet ( P < 0.05). These findings demonstrate that broiler responses to GM are strongly age-dependent and identify phase-specific tolerance thresholds for dietary inclusion. Under the conditions of this study, 4% GM during the starter phase and up to 8% GM during the grower phase can be successfully incorporated when supported by β-mannanase supplementation. This strategy may facilitate the sustainable utilization of guar meal as an agro-industrial by-product while maintaining productive performance and nutrient efficiency in broiler production systems.